Oligodendroglioma pseudoprogression after radiotherapy in a dog: a case report - Rancilio, Nicholas; Drozd, Mary; Donaldson, Logan; Harm, Tyler; Murakami, Keiko (Frontiers in Veterinary Science, 2025)
Pseudoprogression is a clinical and imaging phenomenon characterized by an increase in the size and contrast enhancement pattern of a glioma lesion following treatment with radiotherapy. In human beings, a substantial body of literature describes the phenomenon of pseudoprogression in glioblastoma after radiotherapy. The occurrence of gliomas in the cranial nerves has been reported in human beings as a clinically rare entity. A 7-year-old spayed female French Bulldog was presented with left-sided craniofacial muscle atrophy for a duration of 3 months and episodes of compulsive circling to the left. After a neurological examination, a magnetic resonance (MR) imaging scan of the brain was performed. A T2-and T2 FLAIR-weighted hyperintense, non-contrast-enhancing, T1-weighted hypointense intra-axial suprasellar lesion was found. In addition, an extra-axial, T1-weighted hyperintense, contrast-enhancing mass was identified at the level of the left trigeminal nerve. The lesions were presumptively diagnosed as a glioma and a left trigeminal nerve sheath tumor based on their imaging characteristics and the breed of the patient. A course of stereotactic radiotherapy (SRT) was prescribed, and 3 months after treatment, there was significant progression in the size of the suprasellar mass, indicative of either true progression or pseudoprogression. The left trigeminal nerve mass remained stable in size. Treatment with glucocorticoids resulted in a reduction in the size of the suprasellar mass, as observed on MR imaging 7 months after treatment. The left trigeminal nerve mass remained stable in size. Progression in the size of the suprasellar mass and the left trigeminal nerve mass occurred 9 months after the first course of treatment, and a second course of stereotactic radiotherapy was administered. Sixteen months after the first course of radiotherapy, a necropsy was performed. The suprasellar lesion and the left trigeminal nerve lesion were diagnosed as oligodendrogliomas on histopathology. Trigeminal nerve oligodendrogliomas and pseudoprogression following radiotherapy have not been previously described in dogs. Pseudoprogression should be considered a differential diagnosis for the progression of presumed or confirmed glioma lesions after treatment with radiotherapy. Concurrent oligodendroglioma lesions in the trigeminal nerve are also possible and should be included in the list of differential diagnoses for dogs with concurrent brain lesions.